Supplementing mobile-assisted language learning with reflective journal writing: a case study of Duolingo users' metacognitive awareness - Kessler, Matt (Computer assisted language learning, 2023)
Mobile-assisted language learning (MALL) has witnessed an explosion of interest from consumers and researchers. However, consumers often complain about the limited functionality of MALL applications, which typically do not allow for critical self-reflection or for users to consider different aspects of their learning such as the task itself, the strategies they use, and the challenges they face. Scholars, meanwhile, have argued that MALL research is frequently not grounded in theory, leading to problems with connecting theory and practice. The current study addresses these issues. Drawing upon metacognition theory, this study investigates the implementation of a weekly reflective e-journal writing activity in addition to learners' engagement with the MALL application Duolingo. Over a five-week span, the researcher conducted a case study with six learners, exploring: how the addition of a weekly e-journal activity aided students' metacognitive awareness of aspects of L2 learning; students' perceptions of using reflection journals with MALL; and users' experience with MALL and Duolingo in general. The findings show the journals aided students' metacognitive awareness in five domains, and learners generally reported finding the activity beneficial and enjoyable. Implications are discussed for future research and pedagogy regarding the combination of reflective journaling activities with MALL.